The Advantage of Three Days of Face-To-Face Classes in Grade 12 HUMSS Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the advantages of three days of face-to-face class interms of academic performance, extra-curricular activities, and improving social skills of grade12 HUMSS students.The result of this study reveals that the three days of face-to-face classes have the advantageto grade 12 HUMSS students in terms of their academic performance, extra-curricularactivities, and improving social skills.This study recommended that face-to-face classes are advantageous if the students are usingstrategies to review their lessons and use the library to study. Also, the students should besociable and cooperative when it comes to schoolwork or activities. Lastly, the studentsshould be wise in choosing their circle of friends. They should befriend the students who careabout their academics and those who can make them feel a sense of belonging.
Keywords: Education